Du rapport Durham au « rapport» Brossard : le droit des Québécois à disposer d'eux-mêmes - Chaput, Roger (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
In spite of apparent acceptance by the Imperial government of Durham's recommendation for accelerating the inevitable assimilation of the French culture into its Anglo-Saxon environment, French Canadians nevertheless enjoyed a fair amount of de facto self-government during the years which preceded Confederation. A proof of this is their ability to consolidate during that period the ecclesiastical establishment which was to constitute the core of their social structure for the next century and their success in putting the French language more or less on the same footing as the English language by the repeal of article XLI of the Union Act. Quebeckers were even successful in effecting the codification of their civil laws. All of this however required the active cooperation of the English members of the provincial legislature. A real measure of self-determination was attained by the French as a result of Confederation which gave each province including Quebec exclusive jurisdiction in certain matters. In theory, this new freedom was to be exercised within fairly narrow limits, in view of the federal power to disallow provincial statutes, of the extensive list of federal powers which had priority over a smaller list of provincial powers, and of the federal residual power, not to mention the « general » authority of the federal Parliament. As it turned out, the provinces and therefore Quebeckers enjoyed much more freedom than had been anticipated, as a result of the Privy Council's interpretation of the constitution, a development which to some extent was predictable. The increase in provincial freedom was also due to the political pressure exercised by the provinces themselves. Surprisingly enough, Quebec did not join the « provincial league » at an early hour, Ontario being at first the main defender of provincial autonomy. Quebec's espousal of the provincial cause had to await the removal from power of the Conservatives in the province. The Liberals who took over had voted against Confederation which they regarded as unduly centralized. This in itself would have made them an ally of Ontario. But there was more than that to it. The Quebec Liberals had opposed the 1867 federation from the start (and refused to participate in the 1864 coalition) because they considered that Quebec's freedom might become unduly restrained in a system where she would be faced with numerous partners or provinces, all Anglo-Saxon, instead of having to face an English majority limited to Ontario. It so happened that the Liberals came to power on a wave of profound and widespread dissatisfaction among the French, precisely because of a perceived restriction of their freedoms during the Riel crisis. Hence, the eager look of the people of Quebec towards their own capital as a source of protection against federal encroachment to what they regarded as their legitimate rights. This feeling was reinforced regularly for a period of fifty years as a result first of the Manitoba school question, then the Alberta and Saskatchewan school question, the Keewatin school problem and last but by no means least the Ontario school crisis which this time concerned French schools only. On top of that, came the 1917 conscription to which can be traced the origin of the « modern » separatist movement. During most of that time, the Liberals were in power (1897-1936) and it is no wonder that Quebec gradually became the ever present champion of provincial rights. When Duplessis defeated the Liberals, the trend was so well established that it transcended party lines. Later, the pressure exercised gradually by the separatist movement and the increasing desire of Quebeckers to have more freedom and be masters in their own house led to the Quiet Revolution whose leaders finally asked for a special status. If polls are any indication, it is towards this last approach that a majority of Quebeckers are looking to solve the constitutional question. On the other hand, the right of peoples to self-determination has acquired a wide measure of international recognition since Durham's report which is a far cry from Professor Brossard's recent « report » on the subject as it applies to Quebec, written under the aegis of the Centre de recherche en Droit public of the law faculty of the Université de Montréal. As things now stand, the next step in the determination of Quebec's right to self-government is in the hands of Quebeckers at the forthcoming referendum.